2016
DOI: 10.4049/jimmunol.1600246
|View full text |Cite
|
Sign up to set email alerts
|

ERβ in CD4+ T Cells Is Crucial for Ligand-Mediated Suppression of Central Nervous System Autoimmunity

Abstract: The development of therapies for multiple sclerosis targeting pathogenic T cell responses remains imperative. Previous studies have shown that estrogen receptor (ER) β ligands could inhibit experimental autoimmune encephalomyelitis. However, the effects of ERβ-specific ligands on human or murine pathogenic immune cells, such as Th17, were not investigated. In this article, we show that the synthetic ERβ-specific ligand 4-(2-phenyl-5,7-bis[trifluoromethyl]pyrazolo[1,5-a]pyrimidin-3-yl)phenol (PHTPP) reversed es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In the same study, DHEA was also reported to suppress IL-6 expression by the microglia cell line BV2 (30). Notwithstanding, recent studies by our group revealed that ERb-selective ligands treat established EAE and ongoing Th17 responses (12). Thus, we tested whether DHEA-mediated suppression of established Th17 responses required ERb expression in CD4 + T cells.…”
Section: Dhea Negatively Regulates Th17 Signature Gene Expression Reqmentioning
confidence: 85%
See 3 more Smart Citations
“…In the same study, DHEA was also reported to suppress IL-6 expression by the microglia cell line BV2 (30). Notwithstanding, recent studies by our group revealed that ERb-selective ligands treat established EAE and ongoing Th17 responses (12). Thus, we tested whether DHEA-mediated suppression of established Th17 responses required ERb expression in CD4 + T cells.…”
Section: Dhea Negatively Regulates Th17 Signature Gene Expression Reqmentioning
confidence: 85%
“…Spinal cords were fixed in 10% (v/v) saline-buffered formalin and embedded in paraffin. The 7-mm paraffin-embedded sections were stained with H&E to evaluate spinal cord infiltration, as described previously (12) …”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…Further, DHEA-treated PBMCs from patients with relapsing remitting multiple sclerosis (RR-MS) exhibited decreased IFN-γ, IL-17, IL-4, and IL-2 responses but preserved IL-10. Thus such compounds, which suppress pro-inflammatory cells and expand regulatory subsets, could be useful as therapeutic agents ( 93 ).…”
Section: Estrogen and T Lymphocytesmentioning
confidence: 99%